Hybrid split capacitors and split inductors applied in positive output super‐lift Luo‐converters. Issue 9 (1st November 2013) - Luo, Fang Lin; Ye, Hong
Abstract : Voltage lift technique has been successfully employed in design of DC/DC converters, for example, three series Luo‐converters. However, the output voltage increases in arithmetic progression. Super lift (SL) technique is the most significant contribution in power electronics, for example, four series SL converters. Their output voltage increases in geometric progression. This study introduces a novel approach – SL technique armed by split capacitors and split inductors that implements the output voltage increasing in higher geometric progression. It effectively enhances the voltage transfer gain in power series as well. From the authors experimental results, the power rates of these converters can be few kW.